2022
DOI: 10.1002/cpt.2754
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Pharmacogenetic Testing for Drugs with Clinical Pharmacogenetics Implementation Consortium (CPIC) Guidelines: A Systematic Review

Abstract: The objective of this study was to evaluate the evidence on cost‐effectiveness of pharmacogenetic (PGx)–guided treatment for drugs with Clinical Pharmacogenetics Implementation Consortium (CPIC) guidelines. A systematic review was conducted using multiple biomedical literature databases from inception to June 2021. Full articles comparing PGx‐guided with nonguided treatment were included for data extraction. Quality of Health Economic Studies (QHES) was used to assess robustness of each study (0–100). Data are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 125 publications
1
43
0
Order By: Relevance
“…Costs have previously been highlighted as an important barrier to implementation 8,22,29,51 . However, a recent systematic review by Morris et al reported that most studies (71%) evaluating the costs of pharmacogenetic testing for drugs with CPIC guidelines favoured pharmacogenetic testing over standard of care, 52 which argues for increased utilization of pharmacogenetics for personalized treatment. To enhance the clinical utility and cost savings, pharmacogenetic competence in healthcare and decision support in terms of clear recommendations on specific actions are required.…”
Section: Discussionmentioning
confidence: 99%
“…Costs have previously been highlighted as an important barrier to implementation 8,22,29,51 . However, a recent systematic review by Morris et al reported that most studies (71%) evaluating the costs of pharmacogenetic testing for drugs with CPIC guidelines favoured pharmacogenetic testing over standard of care, 52 which argues for increased utilization of pharmacogenetics for personalized treatment. To enhance the clinical utility and cost savings, pharmacogenetic competence in healthcare and decision support in terms of clear recommendations on specific actions are required.…”
Section: Discussionmentioning
confidence: 99%
“…As of August 2022, an analysis of policies and guidance documents from the top commercial payers and laboratory benefit managers found that 6 out of 12 policies considered DPYD testing medically necessary, and therefore reimbursable (unpublished data). Pharmacoeconomic analyses that consider the costs of DPYD testing and the subsequent savings have found that DPYD screening is cost‐reducing or at worst cost‐effective 9,11,51,52 . A formal Health Technology Assessment from Ontario Health estimated that DPYD testing saves ~ $150 per patient if testing costs $100, 53 yielding a break‐even price of ~ $250, which approximates testing cost in the United States.…”
Section: Assessment Of Dpyd‐fp Association Using the Fda Pharmacogene...mentioning
confidence: 99%
“…For each gene-drug pair, CPIC has reviewed the available evidence linking genotype to phenotype, and assigned a level of evidence (A, A/B, B, B/C, C, C/D, or D). Pharmacogenetics-guided treatments for antidepressants assigned with CPIC evidence levels A and B have been reported to be either cost-effective or cost-saving ( Morris et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%